Turkish adult guardianship in perspective - Kurt, Ekrem (Durham, 2014)
Turkish Adult Guardianship is based upon a triple bond hierarchy. In the first phase the guardian is autharized who is inspected by a family council or the magistrate judge. On top of this hiererchy the supervisory authority, namely the trial judge is located. The person under the guardianship authority may gain the rights and owe within the consent of the guardian who is under gradual inspection of the magistrate and trial judge.
##nofultext##
Keywords: Guardianship; Adult Guardianship; Turkish Adult Guardianship